Risk as a Sustainability Moderator in Islamic Banking Profitability (Pusat Riset dan Inovasi Nasional, 2026)
Risk is an inherent component of all financing activities and must be managed effectively to optimize Islamic banks’ profitability. This study provides insights into how Islamic banks can balance risk and return amid the sector’s evolving challenges by employing panel regression analysis using data from Islamic Commercial Banks (BUS) in Indonesia, sourced from the OJK’s Islamic Banking Statistics. The dataset integrates a ten-year time-series dimension with a cross-sectional dimension covering multiple banks. The findings show that risk moderates both financing performance and profitability outcomes: it weakens the negative effect of problematic financing (PF) on Return on Assets (ROA), while at the same time reducing the positive effect of channeled financing (CF) on ROA. These results suggest that although effective risk management can cushion losses from problematic financing, it may also limit the full profitability gains from financing expansion, underscoring the importance of balanced and integrated risk-return strategies in Islamic banking.